In vivo and in vitro studies of anti-aging properties of Dendrobium sabin flower - Abu, Farahziela (2016)
Exposure to UV radiation has induced reactive oxygen species (ROS) which enhanced the photo-induced aging of the skin characterized by wrinkles appearance. The antioxidant is one of the effective approaches to avoid from photo-induced aging problem. Dendrobium sabin flower was investigated for its antioxidant and anti-aging properties. The oven-dried Dendrobium sabin flower was extracted using 100% methanol (w/v), 100% ethanol (w/v) and 100% water (w/v). The 100% methanolic crude extract showed the highest total phenolic content (40.33 ± mg GAE/g extract) and the best antioxidant properties as showed by DPPH, ABTS and FRAP assays. A correlation relationship between antioxidant activity and total phenolic content showed that phenolic compounds were the dominant antioxidant components in this flower extract. The microbial fermentation on Dendrobium sabin flower showed a potential in increasing the phenolic content and DPPH-scavenging activi ty. The TPC of final fermented medium showed the 18% increment while the DPPH of fermented medium increased significantly to approximately 80% a t the end of the fermentation. The treatment on brine shrimp and human dermal fibroblast primary cell using 100% methanolic crude extract demonstrated insignificant toxicity level. Topical application of 50 mg/ml of 100% methanolic crude extract showed improvement in epidermis and dermis thickness, which was comparable to the positive control treatment effect. The potential of the antioxidant and anti-aging properties found in Dendrobium sabin flower would help in treating undesirable photo-induced aging problems.